1990
DOI: 10.2527/1990.6851469x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of vaginal spaying and anabolic implants on growth and carcass characteristics in beef heifers.

Abstract: Ninety crossbred beef heifers averaging 260 kg were blocked by weight and allotted randomly to 15 pens of six heifers each, with three replicates per treatment. The treatments were spayed heifers (S); intact heifers (I); S + Synovex-H7 (SH); I + Synovex-H (IH); and S + Synovex-S7 (SS). The heifers were spayed vaginally with a Willis instrument; intact heifers were rectally palpated for reproductive soundness. Heifers were fed a growing diet (55 d), re-implanted and subsequently fed a finishing ration (73 or 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
17
0
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 0 publications
8
17
0
1
Order By: Relevance
“…Due to the lack of difference in DMI and the increased ADG in implanted heifers compared to control heifers, G:F was greater for implanted heifers at both d 28 (P = 0.03) and 42 (P = 0.01), but did not differ between d 28 and 42. This finding agrees with previous reports that indicate implantation improves feed efficiency (Adams et al, 1990;Garber et al, 1990).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Due to the lack of difference in DMI and the increased ADG in implanted heifers compared to control heifers, G:F was greater for implanted heifers at both d 28 (P = 0.03) and 42 (P = 0.01), but did not differ between d 28 and 42. This finding agrees with previous reports that indicate implantation improves feed efficiency (Adams et al, 1990;Garber et al, 1990).…”
Section: Resultssupporting
confidence: 83%
“…Therefore, this lack of significance, in relation to gender, could have been due to the fact that implanted OVX heifers exhibited ADG similar to that of implanted intact heifers and was numerically greater than intact control heifers for the initial 28 d of the study (data not reported). This is in agreement with Garber et al (1990), as they found that OVX heifers exhibited a fourfold greater response to implantation than intact heifers. Also, Adams et al (1990) reported that implanting OVX heifers with Synovex-H resulted in BW gains similar to those in intact heifers implanted with Synovex-H.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Other study also revealed no negative influence of laparoscopic ovariectomies on the physical condition of the ewes (TEIXEIRA et al, 2011). The castration of young females is indicated for a faster weight gain in cattle (GARBER et al, 1990). However, other studies found that flank laparotomy (CARVALHO et al, 2010) and transvaginal approach using latex ring for pedicle ligation in cows submitted to ovariectomy (MEIRELLES et al, 2007) caused negative influence concerning post-surgical weight gain.…”
Section: Discussionmentioning
confidence: 88%
“…Ovariectomy is not only performed to prevent pregnancy, but also to reduce problems related to the estrous cycle, such as interference on the weight gain (GARBER et al, 1990;BLEUL et al, 2005 …”
Section: Introductionmentioning
confidence: 99%